An Investigation of Exosome Concentration and Exosomal microRNA (miR-155 and miR-222) Expression in Pregnant Women with Gestational Hypertension and Preeclampsia - Ntsethe A; Mackraj I (Dove Medical Press, 2022)
Aviwe Ntsethe, Irene Mackraj Department of Human Physiology, School of Laboratory Medicine and Medical Sciences, University of KwaZulu-Natal, Durban, South AfricaCorrespondence: Irene Mackraj; Aviwe Ntsethe, Department of Human Physiology, University of KwaZulu-Natal, Durban, South Africa, Tel +27 31-260-7770 ; +27 31-260-7192, Email mackraji@ukzn.ac.za; Ntsethea@ukzn.ac.zaIntroduction: Hypertensive disorders of pregnancy are characterized by widespread maternal endothelial dysfunction. Elevated secretion of exosomes has been associated with endothelial dysfunction. Exosomes play a role in cell-cell communication by transferring microRNAs. These microRNAs are associated with the pathogenesis of hypertensive disorders of pregnancy through the regulation of endothelial function. This study characterizes exosomes and determines exosomal miR-155 and miR-222 expression levels in women with gestational hypertension (GH) and preeclampsia (PE).Methods: Exosomes were isolated and thereafter characterised using NTA, microscopy and ELISA. Results: Exosomes were elevated in the serum of pregnant women with GH and PE (P< 0.05). The circulating exosomes and placental exosomes were increased in both GH and PE (P< 0.0001). The exosomal miR-155 increased in PE but not in GH (P < 0.05). MiR-222 decreased in PE (P < 0.05).Discussion: Elevated exosomes in pregnant women with GH and PE may be indicative of exosomes being potential biomarkers for both GH and PE. The difference in the exosomal miR-155 and miR-222 expression in PE and GH suggested that these two disorders have different pathological pathways.Keywords: exosomes, gestational hypertension, MiR-155, MiR-222, preeclampsia